Answer:
B. <em>y</em> = -3<em>x</em>
Step-by-step explanation:
By reviewing the options:
A. <em>y </em>=<em> </em>3<em>x</em>
when <em>x</em> = -3 --> <em>y</em> = 3(-3) = -9 and the table of values says 9, so this can't be the correct answer.
B. <em>Y </em>= -3<em>x</em>
when <em>x</em> = -3 --> <em>y</em> = -3(-3) = 9 wich is the value of the table, so we check for the next <em>x</em> value.
when <em>x</em> = -1 --> <em>y</em> = -3(-1) = 3 wich is the value of the table, so we check for the next <em>x</em> value.
when <em>x</em> = 0 --> <em>y</em> = -3(0) = 0 wich is the value of the table, so we check for the next <em>x</em> value.
when <em>x</em> = 3 --> <em>y</em> = -3(3) = -9 wich is the value of the table, so we have found the correct answer.
Since B. is valid for every value of <em>x</em> on the thable <em>y</em> = -3<em>x</em> is the answer.